Hippo-Yap Pathway Orchestrates Neural Crest Ontogenesis - Zhao, Xiaolei; Le, Tram P.; Erhardt, Shannon; Findley, Tina O.; Wang, Jun (Frontiers in Cell and Developmental Biology, 2021)
Neural crest (NC) cells are a migratory stem cell population in vertebrate embryogenesis that can give rise to multiple cell types, including osteoblasts, chondrocytes, smooth muscle cells, neurons, glia and melanocytes, greatly contributing to the development of different tissues and organs. Defects in NC development are implicated in many congenital diseases, such as craniofacial aberration and congenital heart diseases. Research on NC development has gained intense interest and made significant progress. Recent studies showed that the Hippo-Yap pathway, a conserved fundamental pathway with key roles in regulation of cell proliferation, survival, and differentiation, is also indispensable for NC development. However, the roles and mechanisms of the Hippo-Yap pathway in NC development remain largely unknown. In this review, we summarize the key functions of the Hippo-Yap pathway on NC induction, migration, proliferation, survival, and differentiation, as well as the diseases caused by its dysfunction in NC cells. We discuss emerging current and future studies in the investigation of the Hippo-Yap signaling in NC development.